A bibliometric profile of Ukrainian Antarctic researches (1997–2007) - V. P. Rybachuk; N. G. Videnina (Ukrainian Antarctic Journal, 2008)
The article contains statistic and bibliometric parameters of scientific works of Ukrainian scientists about Antarctica, published in national and foreign sources during 1997–2007. Database includes 1236 bibliographic descriptions, developed as a result of a specially conducted search. Two main informational streams are identified: articles in journals and periodical collections of articles and presentations at the conferences, which are almost equal by quantity – 609 (49.3 % of total number of publications) and 571 (46.2 %). Both informational massives were formed mainly by publications in national sources (84.7 % of articles and 76.4 % of reports). Articles in “Ukrainian Antarctic Journal” and Conference Materials of National Antarctic Scientific Center of National Academy of Sciences of Ukraine (NASU) are the main materials there – 43.7 % and 62.9 % of total number of national articles and reports correspondingly. There is a positive dynamics in bibliographic massive in general and by the types of documents. During last 5 years, number of articles in journals and collections of articles has been grown steady – more than 70 articles per year, around 60 articles are published in national sources per year, 10-12 articles – in foreign sources. It is shown that authors of publications prefer Russian language. During the last 5 years, the part of English language publications has been also grown and at present it exceeds the number of such publications in Ukrainian language. The article also contains results of bibliometric study of publication productivity of research institutes, universities, and enterprises in Ukraine, included in scientific and research projects and programs related to Antarctica. It is shown that there are just a few scientific institutions and higher educational institutions in Ukraine, who identify directions of studies and contributions and priorities of national Antarctic studies at the world scale. Scientific institutions of NASU play a key role in this process. Rank distribution of the institutions by number of publications do not follow bibliometric model by Zipf law. Large part of joint publications of different scientific insertions can be one of its deformation factors. Two different (by the character) types of their co-operation were identified: real interdisciplinary cooperation and quasi-interdisciplinary (“functional and institutional”) one. Comparative assessments of the priority rank order of antarctic research fields in Ukraine and other countries has been done.The article stresses the need to move to a systematic and target-oriented management of scientific-informational flows of scientific publications of national scientists and relevant metaresources by national and world channels of scientific communication.